Point form: (3,4)
Multiply each equation by the value that make the coefficients of x opposite:
(-4)•(3x-4y)=(-4)(-7)
(3)•(4x+3y)=(3)(24)
Simplify:
-12x+16y=28
12x+9y=72
Add the two equations together to eliminate x from the system:
-12x+16y=28
+12x+9y=72
———————
25y=100
Cancel out the common factor of 25 and divide 100 by 25:
25 100
—- = ——
25 25
100
——
25 Y=4
To find x:
Substitute the value found for y into one of the original equations to find x:
-12x+16(4)=28
Multiply 16 by 4:
-12x+64=28
Subtract 64from 28
-12x=-36
Now cancel out the common factor of -12 ,then divide -36 by -12 which would be x=3